The perception of bicycle crashes with and without motor vehicles: Which crash types do older and middle-aged cyclists fear most?. (May 2020) - Schepers, P.; de Geus, B.; van Cauwenberg, J.; Ampe, T.; Engbers, C.
Highlights: The vast majority of cyclists admitted to hospitals are single-bicycle crash victims. The majority of cyclists believe bicycle-motor vehicle crashes cause most hospitalizations. This perception bias among cyclists is greater in regions with lower bicycle modal shares. Risk perception is affected by cyclists' own crash involvement. Abstract: Several studies have focused on the perceived risk of bicycle crashes (irrespective of crash types) and concluded that cycling near high volumes of motor vehicles deters people from cycling. The perceived risk of bicycle crash types (with or without motor vehicles) has not yet been studied. Cyclists, both in countries with low and high levels of cycling participation, are substantially more likely to sustain severe injuries in single-bicycle crashes than in bicycle-motor vehicle crashes. This questionnaire study sets out to compare which bicycle crash types are perceived to cause most hospitalizations among cyclists. The study comprised cyclists over 55 years in the Netherlands, and over 40 years in the Belgian regions of Flanders (a region with high cycling participation), Brussels and Wallonia (regions with low cycling participation). The majority of cyclists (60%) perceive bicycle-motor vehicle crashes cause most hospitalizations among cyclists. This percentage is greatest in the areas of Brussels and Wallonia and lowest in the Netherlands. Cyclists who were involved in a bicycle-motor vehicle crash themselves are more likely to regard this crash type as the most common cause of hospitalizations among cyclists, while cyclists over 60 years who were involved in a crash without a motor vehicle are more likely to perceive that crash type as the most common cause. The smaller perception bias in the study areas with higher cycling participation – particularly the Netherlands and to a somewhat lesser degree Flanders – is probably due to bicycle infrastructure being more separated from high-speed motor traffic, leaving cyclists less exposed. The outcomes show that cyclists underestimate the likelihood of severe injuries due to single-bicycle crashes. New interventions should raise the awareness of the risk of single-bicycle crashes and provide solutions to avoid such crashes.